2010
DOI: 10.1007/s13157-010-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Do Hydrologic Regimes Used in Rice Fields Compromise the Viability of Resting Stages of Aquatic Invertebrates?

Abstract: Irrigated rice fields in southern Brazil remain without surface water for 2 years during the fallow phase. The present study tested the hypothesis that the hydrologic regime adopted in rice fields of southern Brazil does not compromise the viability of resting stages of aquatic invertebrates. Dry sediment samples were collected from 9 rice fields with different durations of the fallow phase: 20 days, 1 year, and 2 years after the harvesting period. A total of 2,853 invertebrates distributed across 40 taxa emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…In some warmer regions, two or three crops a year are produced (Van Arsdale and Lewis, 1995), while in cooler areas a yield of one crop a year results in a longer fallow period of up to eight months. Brazilian rice fields typically have a fallow stage lasting two years to restore soil fertility, increase soil organic content and suppress weeds (Stenert et al, 2010).…”
Section: The Rice Field Habitatmentioning
confidence: 99%
See 2 more Smart Citations
“…In some warmer regions, two or three crops a year are produced (Van Arsdale and Lewis, 1995), while in cooler areas a yield of one crop a year results in a longer fallow period of up to eight months. Brazilian rice fields typically have a fallow stage lasting two years to restore soil fertility, increase soil organic content and suppress weeds (Stenert et al, 2010).…”
Section: The Rice Field Habitatmentioning
confidence: 99%
“…Ostracods are ideally suited to exploit rice fields, which is why they are often the dominant group in the rice field environment (Roger, 1996). Many rice field ostracods have desiccation-resistant eggs (Horne and Martens, 1998;Stenert et al, 2010), their carapaces help to retain moisture during periods of drought and protect them from UV radiation (Van den Broecke et al, 2012), they have a short life cycle, and they consume organic detritus, algae and cyanobacteria, all prolific in rice fields.…”
Section: The Rice Field Habitatmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice fields are considered man made habitats for many species of aquatic plants, invertebrates, amphibians and birds throughout the world, especially during the rice growth period (Czech and Parsons 2002;Bambaradeniya and Amerasinghe 2004;Elphick and Oring 2003). Some studies in southern Brazil have also shown that most of the regional aquatic biota utilizes these ecosystems as temporary habitats Rolon and Maltchik 2010;Stenert et al 2010;Maltchik et al 2011;Guadagnin et al 2012;Linke et al 2014;Moreira and Maltchik 2014). The presence of these organisms in these ecosystems has attracted the attention of researchers involved with species conservation, especially in the attempt to discover which rice cultivation practices have the lowest impact on species diversity in the agricultural matrix.…”
Section: Introductionmentioning
confidence: 99%
“…When rice field managers in California flooded their fields after harvest to accelerate straw decomposition, more habitat was created for aquatic birds (Elphick and Oring 2003). Studies have shown that rice plots that maintained water during the offseason period had different compositions of macrophytes, invertebrates and amphibians than plots that were drained for livestock Rolon and Maltchik 2010;Stenert et al 2009Stenert et al , 2010.These researchers emphasize that maintaining water in some fields during the off-season period could be a strategy for promoting greater biodiversity in the agricultural matrix .…”
Section: Introductionmentioning
confidence: 99%